Oral propranolol for the treatment of hemangiomas in high-risk infants: safety and cost analysis of outpatient-initiated therapy - Su, Rina; Qian, Hua; Hu, Cui; Li, Wei; Li, JiBin; Wu, Bo; Gu, Yang; Zhang, Ting; Wu, YaFen; Qian, YingYing; Lu, Hui (Frontiers in Medicine, 2024)
Objectives To investigate the safety and cost analysis of oral propranolol treatment for high-risk infantile hemangiomas starting from the outpatient setting. Methods A total of 41 high-risk infantile hemangioma patients from outpatient settings and 43 from inpatient settings were selected for the study. After routine pre-treatment examinations, patients were administered propranolol in a stepwise incremental dosing regimen over three consecutive days in the outpatient clinic. Changes in heart rate, blood pressure and PR interval before and after medication were compared. On the 10th day post-medication, liver and kidney functions, fasting blood glucose, tumor ultrasonography, and electrocardiogram were re-evaluated. The costs of treatment starting from the outpatient clinic (including pre-treatment examinations and the first three days of treatment) were calculated and compared with those of similarly managed inpatient cases. Results The majority of patients exhibited a reduction in heart rate and blood pressure, as well as an extended PR interval after treatment of medication (P < 0.05), which remained within normal limits without clinical symptoms. On the 10th day post-medication, statistical differences in blood biochemistry and electrocardiograms were observed when compared to pre-treatment values (P < 0.05), but all values remained within normal ranges. No severe adverse reactions such as hypoglycemia occurred. Additionally, the cost of treatment from the outpatient clinic was significantly lower than that of inpatient care. Conclusion Oral propranolol treatment for high-risk infantile hemangiomas starting from the outpatient setting is associated with few adverse reactions and significantly reduced treatment costs. It is worthy of broader application in hospitals without dermatology wards.